2012
DOI: 10.1292/jvms.12-0180
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Thermal Cameras with Canine Hip Area Thermographic Images

Abstract: ABSTRACT. The objective of this study was to compare the method of thermography by using three different resolution thermal cameras and basic software for thermographic images, separating the two persons taking the thermographic images (thermographers) from the three persons interpreting the thermographic images (interpreters). This was accomplished by studying the repeatability between thermographers and interpreters. Forty-nine client-owned dogs of 26 breeds were enrolled in the study. The thermal cameras us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
1
13
0
5
Order By: Relevance
“…Long-haired dogs show minimal temperature loss by convection, so, the coat acts as an insulator, preventing dissipation of infrared radiation from the body. This justifies the findings from the present study and has been recognized and discussed by several authors (EDDY et al 2001;TUNLEY & HENSON, 2004;LOUGHIN & MARINO, 2007;INFERNUSO et al 2010;VAINIONPÄÄ et al 2012) and observed in multiple species, such as horses, llamas, and dogs. However, despite this influence being recognized by most authors, there has no comparative study quantifying the findings.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Long-haired dogs show minimal temperature loss by convection, so, the coat acts as an insulator, preventing dissipation of infrared radiation from the body. This justifies the findings from the present study and has been recognized and discussed by several authors (EDDY et al 2001;TUNLEY & HENSON, 2004;LOUGHIN & MARINO, 2007;INFERNUSO et al 2010;VAINIONPÄÄ et al 2012) and observed in multiple species, such as horses, llamas, and dogs. However, despite this influence being recognized by most authors, there has no comparative study quantifying the findings.…”
Section: Discussionsupporting
confidence: 93%
“…In addition to the thermal insulation, it also caused difficulties in marking areas of interest due to loss of anatomical references. Similarly, a previous study (VAINIONPÄÄ et al 2012) noted that the hair length and type can compromise the examination due to the loss of anatomic references to define the areas evaluated. Thermographic cameras that capture photographs simultaneously as the thermal image, as done in this study, help to identify anatomical references.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…There are several studies on the use of thermal imaging in canines. The ability to obtain consistent thermographic images in healthy dogs has been demonstrated (12,13). Thermal imaging has been shown to be useful in detection of several pathological conditions in dogs including osteosarcoma (14), elbow dysplasia (15), cranial cruciate ligament rupture (16,17), and intervertebral disc disease (18).…”
Section: Introductionmentioning
confidence: 99%